Konsep dan Gerakan Tawhîd dalam Perspektif Antropologi Agama - Basyir, Kunawi (Religió: Jurnal Studi Agama-agama, 2014)
One of the special characteristic of religion is transcendent, holy, absolute and permanent due to the holy revelation of the divinity and culture is human creation in forms of relativity due to its dynamic characteristic. Human culture will take a sort of changing in accordance with the time and space they lived in. Human will have understanding in accordance with their capability and experience in responding and practicing dogma according to their belief. In this point, they try to return to their original form of being oneness or ummah wâh}idah either in social and theological fields. The concept of ummah wâh}idah is well known with the tawhîd movement focused on theological and social realm. This paper attempts to see the religious movement of tawhîd Muh}ammad in anthropological perspective. It aims to respond the exclusive religious understanding of some groups in Indonesia in threatening plurality and social integration. The paper suggests that the movement of tawhîd Muh}ammad is a theological and social movement. Theological movement maintains that all Semitic religions should be tied up with the idea of millah Ibrâhîm, not Islamic religion (aqîdah Islâmîyah) as many salafism argue in the recent days. Besides, the social movement of tawhîd Muh}ammad means that tawhîd could unite many groups and ethnics of Arab tribes to build a new face of civilization in more civilized and dynamic.